DOKUMENTASI PENGGUNA SISTEM SKRINING “ANAK TANGGUH”, MEDIA SKRINING DIGITAL AUTISME BERBASIS M-CHAT-R/F DI INDONESIA - Rohmah, Arini Nur; Aji Ari Adam; Prilya Shanty Adrianie; Ariefin Nur Hidayat; Amri Zadi Hudaya; Galardhia Zain Azzahra; Naila Khairunnisa; Dedi Gunawan; Yusuf Sulistyo Nugroho (Jurnal Manajemen dan Teknologi Informasi, 2025)
There is an increasing prevalence of Autism among Indonesian children. However, limited access, cost, and the lack of Indonesian-language screening tools present significant challenges for parents in the early detection of children with autism. A web-based digital system known as the "Sistem Skrining Anak Tangguh", has been developed in Indonesia. This system employs the M-CHAT-R/F (Modified Checklist for Autism in Toddlers, Revised with Follow-Up) method, which is a well-established tool for autism screening. The potential impact of this system is significant, as it could provide a comprehensive and efficient screening tool for autism in Indonesia. The system has been designed to offer all of its functions in Indonesian-language to increase accessibility and understanding among Indonesians. The system is accessible via web browser, enabling parents to conduct screening independently, at any time and from any location. However, a search for user documentation on the website has not yielded any results. The objective of this research project is to produce user documentation for the Sistem Skrining Anak Tangguh. The present user documentation is expected to engender a number of benefits. It is anticipated that an increase in the utilisation of the screening site will result in enhanced efficacy of its usage by users. This is expected to evolve into a comprehensive solution that will broaden the scope of early autism screening in Indonesia.